Effects of Tannic Acid on Cisplatin-Induced Changes in Poly(ADP-Ribose) Polymer Turnover in Rat Liver and Thymocyte Nuclei (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: Cisplatin is a powerful antineoplastic drug widely used in the therapy of cancer patients. To attenuateundesirable side effects of the drug, chemotherapeutic regimens are employed based on the use of antioxidantsupplementation. The goal of the present study is the examination of the impact of cotreatment with cisplatinand tannic acid (TA) on key members involved in poly(ADP-ribose) polymer (pPARr) turnover in rat liver andthymocyte nuclei, i.e., poly(ADP-ribose)polymerase 1 (PARP 1) activity, poly(ADP-ribose)glycohydrolase(PARG), and NAD+ content. Materials and Methods: Wistar albino rats were randomly distributed in fourgroups: Control group, treated with cisplatin, tannic acid, and cotreated with tannic acid and cisplatin. The drugswere injected intra-peritoneal. Animals were treated according to regulations of National Centre of Bioethics(Armenia). Cell nuclei were isolated according to standard procedure. PARP 1 activity was evaluated by NAD+consumption. PARG protein was estimated by sandwich Elisa method. Data are expressed as mean Â± s.d. Statisticaldifferences in the results between groups were evaluated by the Studentâ€™s t-test. A probability (P) value of < 0.05was considered significant. Key Results: Cisplatin and tannic acid displayed hepatotoxic effects in rat liver in 48h after treatment. Although treatment of rats either with cisplatin or TA downregulated NAD+ and PARG contentin liver nuclei, the drugs exhibited oppositely directed effects on PARP 1 activity. Cotreatment with cisplatinand TA-stimulated PARP 1 activity in liver nuclei did not affect the basal level of NAD+ and prevented drasticdecrease in PARG protein level. Conclusions: Cisplatin-induced inhibition of PARP 1 activity, NAD+, and PARGcontent in liver nuclei were eliminated after cotreatment of rats with tannic acid.